Organisation and structural constraints of the catfish supply chain in Côte d’Ivoire - Niamien, Kadjo Henri Joel (Geografares, 2026)
In Côte d’Ivoire, catfish remains marginal in aquaculture despite real consumption potential and strong dependence on fish imports. This article examines the organisation and structural constraints of its supply chain. The study combines a quantitative survey of 200 fish farmers and 38 fishers with semi-structured interviews conducted with 128 actors across the chain. Results show a triply fragmented structure: weak and poorly specialised local aquaculture production, continental catches that remain largely invisible in official statistics, and growing dependence on imported Asian siluriforms. The sector operates mainly through informal relations, with no contractualisation or vertical coordination. Catfish is also constrained by persistent food taboos. Together, these factors maintain a structural lock-in. The article argues for integrated governance linking input provision, market structuring and the sociocultural revalorisation of the product.
Keywords: Ivory Coast; catfish; supply chain; structural constraints